THE ANALYSIS OF SCHOOL OPERATIONAL SUPPORT FUNDS’ EFFECTIVENESS - Esti Rahayu; Mimin Nur Aisyah (Jurnal Pendidikan Akuntansi Indonesia, 2018)
This research aims to determine the effectiveness of the use of BOS funds in SMK Negeri 2 Magelang in 2016 and its SWOT analysis. It was a descriptive research with quantitative and qualitative approach. Data collection methods used were interview and documentation. The research found that the use of BOS funds in SMK Negeri 2 Magelang in 2016 amounted to Rp1,279,348,659.00 from the planned Rp1,614,911,317.00 with the effectiveness of 79%. According to the criteria of the Ministry of National Education (2009), the use of BOS funds is categorized as very effective because the percentage exceeds 70%. The SWOT analysis provides several strategies, including : (1) using BOS funds to improve the competence of students and teachers and thus enhancing school’s existence and achievement (S-O strategy), (2) administering training and capacity building of human resource managers (W-O strategy), (3) improving the internal control and communication with government related to BOS fund management (S-T strategy), and (4) increasing the supervision on the management of BOS funds (W-T strategy). Keywords: Effectiveness, BOS funds, SWOT analysis, BOS strategy